The Effectiveness of Stock Hedging with Cryptocurrency in the Indonesian Capital Market Pre-Pandemic, Pandemic and Post-Pandemic Periods - Tantowi Jauhari; Zaäfri Ananto Husodo (Green Publisher Indonesia, 2025)
This study analyzes the effectiveness of Bitcoin and Ethereum as hedging instruments for LQ45 stock portfolios in Indonesia over three market periods: pre-pandemic (2018–2020), pandemic (2020–2022), and post-pandemic (2023–2024). The research applies GARCH(1,1) to estimate stock volatility and the DCC-GARCH model to measure dynamic correlations with cryptocurrencies. Hedge effectiveness is assessed using the Hedge Effectiveness Index (HEI). The findings show that both Bitcoin and Ethereum failed to reduce portfolio risk in Indonesia, with HEI values mostly negative throughout all periods. The implication is that these cryptocurrencies tend to increase volatility rather than serve as effective hedging tools. The study recommends traditional assets or stablecoins as more reliable alternatives for Indonesian investors.